2010
DOI: 10.1007/s10551-011-0797-x
|View full text |Cite
|
Sign up to set email alerts
|

Discouraging Bullying: The Role of Ethical Leadership and its Effects on the Work Environment

Abstract: bullying, ethical leadership, workload, work conditions,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 42 publications
8
113
1
8
Order By: Relevance
“…An increasing amount of research has supported the significant impact of ethical leadership (Brown, Treviño, & Harrison, 2005), on follower outcomes, including follower job performance (Piccolo, Greenbaum, Hartog, & Folger, 2010;Walumbwa, Morrison, & Christensen, 2012;Walumbwa, Mayer, Wang, Wang, Workman, & Christensen, 2011) , voice (Avey, Palanski, & Walumbwa, 2011;Brown, et al, 2005;Walumbwa & Schaubroeck, 2009), and other positive (Kacmar, Bachrach, Harris, & Zivnuska, 2011;Mayer, Aquino, Greenbaum, & Kuenzi, 2012;Mayer, Kuenzi, Greenbaum, Bardes, & Salvador, 2009;Schaubroeck, Hannah, Avolio, Kozlowski, Lord, Trevino, Dimotakis, & Peng, 2012), and negative behaviors (Mayer et al, 2012;Stouten et al, 2010). Recently, more attention has been paid to understanding the mediating mechanisms that underlie these relationships.…”
Section: Ethical Leadership and Follower Voice And Performance: The Rmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing amount of research has supported the significant impact of ethical leadership (Brown, Treviño, & Harrison, 2005), on follower outcomes, including follower job performance (Piccolo, Greenbaum, Hartog, & Folger, 2010;Walumbwa, Morrison, & Christensen, 2012;Walumbwa, Mayer, Wang, Wang, Workman, & Christensen, 2011) , voice (Avey, Palanski, & Walumbwa, 2011;Brown, et al, 2005;Walumbwa & Schaubroeck, 2009), and other positive (Kacmar, Bachrach, Harris, & Zivnuska, 2011;Mayer, Aquino, Greenbaum, & Kuenzi, 2012;Mayer, Kuenzi, Greenbaum, Bardes, & Salvador, 2009;Schaubroeck, Hannah, Avolio, Kozlowski, Lord, Trevino, Dimotakis, & Peng, 2012), and negative behaviors (Mayer et al, 2012;Stouten et al, 2010). Recently, more attention has been paid to understanding the mediating mechanisms that underlie these relationships.…”
Section: Ethical Leadership and Follower Voice And Performance: The Rmentioning
confidence: 99%
“…Keywords: Ethical leadership; relational identification; organizational identification; voice; implicit theory of morality (Mayer et al, 2012;Stouten et al, 2010). Recently, more attention has been paid to understanding the mediating mechanisms that underlie these relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Either implicitly or explicitly, leaders communicate the core values that shape the behaviors of employees. On the other hand, when leaders fail to communicate positive values or fail to act on situations that violate them, the quality of the psychosocial work environment deteriorates and employee performance and wellbeing suffer (Ingersoll, Olsan, Drew-Cates, DeVinney & Davies, 2002;Kelloway & Day, 2005;Stouten et al, 2010). Positive supportive leadership is critical to promoting effective working relationships among employees (Burke et al, 2006;Kuoppala, et al, 2008;Wendt, Frisina, & Rothgang, 2009).…”
Section: Turnover Intent In New Nursesmentioning
confidence: 99%
“…Recent research has shown that supportive leadership styles tend to be associated with lower levels of workplace bullying (Hauge, Skögstad & Einarsen, 2007;Hauge at al. 2011;Hoel, Glaso, Cooper, & Einarsen, 2010;Stouten et al, 2010). For example Hauge et al (2007) and Hoel et al (2010) found that negative and what are often labelled 'non-leadership' behaviors (laissez-faire and non-contingent leadership) encourage workplace bullying, whereas positive, relationally-focused leadership styles,…”
Section: Turnover Intent In New Nursesmentioning
confidence: 99%